Time-Domain Minimization of Voltage and Current Total Harmonic Distortion for a Single-Phase Multilevel Inverter with a Staircase Modulation - Milan Srndovic; Yakov L. Familiant; Gabriele Grandi; Alex Ruderman (Energies, 2016)
This paper presents the optimization technique for minimizing the voltage and current total harmonic distortion (THD) in a single-phase multilevel inverter controlled by staircase modulation. The previously reported research generally considered the optimal THD problem in the frequency domain, taking into account a limited harmonic number. The novelty of the suggested approach is that voltage and current minimal THD problems are being formulated in the time domain as constrained optimization ones, making it possible to determine the optimal switching angles. In this way, all switching harmonics can be considered. The target function expression becomes very compact and existing efficient solvers for this kind of optimization problems can find a solution in negligible processor time. Current THD is understood as voltage frequency weighted THD that assumes pure inductive load—this approximation is practically accurate for inductively dominant RL-loads. In this study, the optimal switching angles and respective minimal THD values were obtained for different inverter level counts and overall fundamental voltage magnitude (modulation index) dynamic range. Developments are easily modified to cover multilevel inverter grid-connected applications. The results have been verified by experimental tests.